PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISIONS) TERHADAP KEMAMPUAN MENULIS SISINDIRAN PADA SISWA KELAS XI SMA NEGERI 1 CILIMUS - Sagita, Azkia Fitri; Ropiah, Opah (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
The STAD (Student Team Achievement Divisions) cooperative learning model is the simplest cooperative learning model that involves students participating in small groups. This study aims to describe the effect of the STAD learning model on the writing skills of students in Grade XI at SMA Negeri 1 Cilimus. This is a quantitative study. The research method used is an experiment with a pretest-posttest control group design. The instruments used in this study are pretest and posttest questions. Data collection techniques include observation, literature review, documentation, and testing. Data analysis techniques used expert validity tests, data normality tests, homogeneity tests, and hypothesis testing using the Independent Sample T-Test. Before the implementation of the STAD model, only 2 out of 35 students in the experimental and control classes achieved the Minimum Passing Criteria (KKM) of 75. After implementation, the number of students in the experimental class who achieved the KKM increased to 32, with the average score rising from 36.69 to 85.03. Meanwhile, in the control class using the lecture method, only 8 students achieved the KKM, with the average score increasing from 36.54 to 65.00. The hypothesis test used an Independent Sample Test with a significance value of 0.000 < 0.05, which means that there is a significant difference between the two classes. These results show that there is a significant effect before and after using the STAD cooperative learning model on the writing skills of students in Class XI at SMA Negeri 1 Cilimus.